2021
DOI: 10.1088/1361-6382/ac37a5
|View full text |Cite
|
Sign up to set email alerts
|

New metric reconstruction scheme for gravitational self-force calculations

Abstract: Inspirals of stellar-mass objects into massive black holes will be important sources for the space-based gravitational-wave detector LISA. Modelling these systems requires calculating the metric perturbation due to a point particle orbiting a Kerr black hole. Currently, the linear perturbation is obtained with a metric reconstruction procedure that puts it in a “no-string” radiation gauge which is singular on a surface surrounding the central black hole. Calculating dynamical quantities in this gauge involves … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…In both cases, it would be valuable to connect more closely and in more generality to the large literature on solutions to the wave equation on a rotating black hole background [89,96,97,115]. This could include using higher-spin fields and making contact to the Teukolsky equation [116], as opposed to the scalar wave equations used here, considering other modifications to the wave equations, as for example in modified theories of gravity or black holes [68,[117][118][119][120][121][122][123][124], the introduction of sources [125,126], investigating how to describe caustics as well as the propagator and scattering on the black hole background more generally [127][128][129][130][131].…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, it would be valuable to connect more closely and in more generality to the large literature on solutions to the wave equation on a rotating black hole background [89,96,97,115]. This could include using higher-spin fields and making contact to the Teukolsky equation [116], as opposed to the scalar wave equations used here, considering other modifications to the wave equations, as for example in modified theories of gravity or black holes [68,[117][118][119][120][121][122][123][124], the introduction of sources [125,126], investigating how to describe caustics as well as the propagator and scattering on the black hole background more generally [127][128][129][130][131].…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, it would be valuable to connect more closely and in more generality to the large literature on solutions to the wave equation on a rotating black hole background [89,96,97,116]. This could include using higher-spin fields and making contact to the Teukolsky equation [117], as opposed to the scalar wave equations used here, considering other modifications to the wave equations, as for example in modified theories of gravity or black holes [68,[118][119][120][121][122][123][124][125][126][127], the introduction of sources [128,129], investigating how to describe caustics as well as the propagator and scattering on the black hole background more generally [130][131][132][133][134]. To do so, it will be important to understand the matched asymptotic expansion that embeds the plane wave into the full spacetime, and the respective interplay between the 'far-zone' outer spacetime and the 'near-zone' plane wave.…”
Section: Discussionmentioning
confidence: 99%
“…non-vacuum) case by augmenting the metric perturbation with a so-called corrector tensor, which is determined by solving certain decoupled ODEs by integrating over the outgoing Kerr-Newman radial coordinate. Toomani et al [46] have shown that the gauge singularities arising in the GHZ approach can be softened by moving to a 'shadowless' gauge, in order to obtain a metric perturbation suitable as an input for second-order calculations. This approach is certainly promising, and is under active development.…”
Section: Introductionmentioning
confidence: 99%